Reflections of a clinical psycholpathologist as practitioner and researcher. [article]. - Carandang, Ma. Lourdes Arellano.. .
This paper has two parts. The first part articulates the concerns of the author as a clinical practitioner and researcher. She cites the utility of conceptualizations derived from clinical experience and observations. She stresses the need to invent new methods that do not delimit clinical data and experience. The second part presents preliminary findings from an ongoing research project on sexuality abused children. It aims to formulate useful recommendations for the understanding and rehabilitation of the victimized children. It serves as an example of how the practitioner can contribute to clinical research.